Law Enforcement In The Field Of Music In The Spotify Application Program (Journal of Private and Commercial Law, 2021)
Music and songs are one of the areas of Intellectual Property Rights which are protected in Article 58 letter (d) of UU Number 28 of 2014 about Copyright, namely Copyright Protection for Song or music creations with or without text. In this digital era, there are many ways for us to get the music we want through various platforms on the internet such as Youtube, Joox, Spotify, and others. Because the means to get music are getting easier now, there are more and more copyright violations against music, ranging from piracy to plagiarism. This study aims to discuss how the Copyright law regulates copyright protection in the field of music on the internet and also how the Spotify music service platform protects copyright. The research method used is a normative research method; the data analyzed is secondary legal data consisting of primary legal materials, namely Copyright Law and Secondary Law materials, namely literature related to research problems. Based on the results of the study, it is known that Spotify as one of the world's famous song streaming applications has the exclusive right as a copyright licensee to exercise exclusive rights as regulated in Article 9 of the Copyright Law. Spotify as a streaming service provider must of course have a license for the music or songs provided in the application through a license agreement with the licensor.